Shetland. Season four [videorecording (DVD)] - Henshall, Douglas, 1965-; Robertson, Steven; O'Donnell, Alison; Cleeves, Ann (BBC Worldwide Ltd. : ITV Studios Limited, 2018)
Follows DI Jimmy Perez and his DS, "Tosh" MacIntosh, as they investigate how the cold case of a teenager's murder is linked to their current investigation of a journalist's murder.